Tanshinone IIA Exerts Anti-Inflammatory and Immune-Regulating Effects on Vulnerable Atherosclerotic Plaque Partially via the TLR4/MyD88/NF-κB Signal Pathway - Zhuo Chen; Xiang Gao; Yang Jiao; Yu Qiu; Anlu Wang; Meili Yu; Fangyuan Che; Siming Li; Jing Liu; Jingen Li; He Zhang; Changan Yu; et al. (Frontiers Media S.A., 2019)
Background: Tanshinone IIA (Tan IIA), a lipophilic constituent from Salvia miltiorrhiza Bunge, has shown a promising cardioprotective effect including anti-atherosclerosis. This study aims at exploring Tan IIA's anti-inflammatory and immune-regulating roles in stabilizing vulnerable atherosclerotic plaque in ApoE-deficient (ApoE−/−) mice.Methods: Male ApoE−/− mice (6 weeks) were fed with a high-fat diet for 13 weeks and then randomized to the model group (MOD) or Tan IIA groups [high dose: 90 mg/kg/day (HT), moderate dose: 30 mg/kg/day (MT), low dose: 10 mg/kg/day (LT)] or the atorvastatin group (5 mg/kg/day, ATO) for 13 weeks. Male C57BL/6 mice (6 weeks) were fed with ordinary rodent chow as control. The plaque stability was evaluated according to the morphology and composition of aortic atherosclerotic (AS) plaque in H&E staining and Movat staining sections by calculating the area of extracellular lipid, collagenous fiber, and foam cells to the plaque. The expression of the Toll-like receptor 4 (TLR4)/myeloid differentiation factor88 (MyD88)/nuclear factor-kappa B (NF-κB) signal pathway in aorta fractions was determined by immunohistochemistry. Serum levels of blood lipid were measured by turbidimetric inhibition immunoassay. The concentrations of tumor necrosis factor-α (TNF-α) and monocyte chemoattractant protein-1 (MCP-1) were detected by cytometric bead array.Results: Tan IIA stabilized aortic plaque with a striking reduction in the area of extracellular lipid (ATO: 13.15 ± 1.2%, HT: 12.2 ± 1.64%, MT: 13.93 ± 1.59%, MOD: 18.84 ± 1.46%, P < 0.05) or foam cells (ATO: 16.05 ± 1.26%, HT: 14.88 ± 1.79%, MT: 16.61 ± 1.47%, MOD: 22.08 ± 1.69%, P < 0.05) to the plaque, and an evident increase in content of collagenous fiber (ATO: 16.22 ± 1.91%, HT: 17.58 ± 1.33%, MT: 15.71 ± 2.26%, LT:14.92 ± 1.65%, MOD: 9.61 ± 0.7%, P < 0.05) to the plaque than that in the model group, concomitant with down-regulation of the protein expression of TLR4, MyD88, and NF-κB p65, and serum level of MCP-1 and TNF-α in a dose-dependent manner. There were no differences in serum TC, LDL, HDL, or TG levels between ApoE-/- mice and those treated with atorvastatin.Conclusions: These results suggest that Tan IIA could stabilize vulnerable AS plaque in ApoE−/− mice, and this anti-inflammatory and immune-regulating effect may be achieved via the TLR4/MyD88/NF-κB signaling pathway.